Surgical outcome of epicanthus and telecanthus correction by C-U medial canthoplasty with lateral canthoplasty in treatment of Blepharophimosis syndrome - Ahmed Ali Amer; Marwa Mahmoud Abdellah; Nader Hussein Fouad Hassan; Amr Mounir (BMC Ophthalmology, 2022)
Abstract Purpose To evaluate the surgical outcome of epicanthus and telecanthus correction by C-U medial canthoplasty with lateral canthoplasty in Blepharophimosis Syndrome. Patients and methods This was a retrospective single arm interventional study including 18 eyes of 9 patients with Blepharophimosis-ptosis-epicanthus inversus syndrome who presented to oculoplastic clinic, ophthalmology department, Qena university hospital in the period of between July 2020 to April 2021. All the patients had BPES with epicanthus and telecanthus. All cases were subjected to by C plasty with medial and lateral canthoplasty for correction of epicanthus and telecanthus correction followed by frontalis suspension surgery to correct the co-existing blepharoptosis. Results The study included 9 cases of BPES, 6 boys and 3 girls, the mean age was 5.4 ± 1.5 in the study group, all patients had a positive family history for BPES. After surgery, the mean IICD decreased from 38.44 mm preoperatively to 32.8 mm postoperatively, with a mean difference of 6.2 mm (P <  0.001). Likewise, the mean PFL increased from 20.78 mm preoperatively to 26.63 mm postoperatively, with a mean difference of 5.8 mm (P <  0.001). Epicanthus skin fold disappeared in all cases and medical canthus could be seen with well healed difficulty seen scars. Conclusion C-U medial canthoplasty with lateral canthoplasty in Blepharophimosis Syndrome was found to be an effective procedure in the correction of epicanthus and telecanthus.